EDUKASI PEER-TO-PEER LENDING SYARIAH SEBAGAI ALTERNATIF PERMODALAN BAGI USAHA MIKRO KECIL DAN MENENGAH DESA CIWALEN PANJALU - Mirza Hedismarlina Yuneline (Jurnal Berdaya Mandiri, 2022)
The condition of the Covid-19 pandemic is also a condition in which MSMEs start to use financial technology for their operational interests. Since 2016, the user ofÂ  payment-based-fintech are 38%, while those who access deposits, lending, and capital raising-based-fintech are 31%. However, the increase is not accompanied by a good level of financial literacy education. There is a technology gap between urban and rural communities and also between users at a young age and over 35 years. The solution to the problem offered is by providing technology literacy education by introducing the financial technology industry to rural communities, especially for MSMEs in Ciwalen Panjalu Village. The purpose of this community service is introducing the importance of capital in business, fintech operational, educating of financial literacy and demonstrating to the MSMEs on the Sharia Peer-to-Peer Lending platform. The method of implementation starts with a needs analysis, the initial questionnaire, core activities, the final questionnaire, and the evaluation.